Acupuncture for Relieving Abdominal Pain and Distension in Acute Pancreatitis: A Systematic Review and Meta-Analysis - Zhu, Fengya; Yin, Shao; Zhu, Xinyun; Che, Deya; Li, Zimeng; Zhong, Yue; Yan, Hui; Gan, Daohui; Yang, Lanying; Wu, Xiaohan; Li, Liuying (Frontiers in Psychiatry, 2021)
Abstract BACKGROUND Clinical evidence suggests that acupuncture is effective for relieving abdominal pain and distension in acute pancreatitis (AP), but there is a lack of systematic reviews (SRs) and meta-analyses (MAs) that provide high-quality evidence of its efficacy and safety. AIM To assess the efficacy and safety of acupuncture in relieving abdominal pain and distension in AP. METHODS We searched PubMed, Web of Science, the Cochrane Library, CNKI, and Wanfang, VIP, and China Biomedical Literature databases. Randomized controlled trials of acupuncture plus routine treatment (RT) versus RT alone or RT plus sham/placebo acupuncture were included. Primary outcomes included total effectiveness rate, VAS scores for abdominal pain and distension, and time until relief of abdominal pain and distension. Secondary outcomes included time until recovery of bowel sound, time until first defecation, length of hospital stay, and APACHE II score. RESULTS Finally, 19 eligible original studies (n = 1503) were included. The results showed that acupuncture combined with RT had a significant advantage in increasing the total effectiveness rate (risk ratio: 1.15; 95% confidence interval [CI]: 1.06–1.24; P = 0.001). Acupuncture also reduced the VAS score for abdominal pain (weighted mean difference [WMD]: −1.45; 95% CI: −1.71 to −1.19; P < 0.0001) and the VAS score for abdominal distension (WMD: −0.71; 95% CI: −1.04 to −0.37; P < 0.0001) in AP patients. Other results also showed the efficacy of acupuncture. One study reported adverse events after acupuncture. CONCLUSION RT combined with acupuncture has a better effect than RT alone for relieving abdominal pain and distension in AP. More rigorous studies are needed to confirm this result. Registration: PROSPERO CRD42019147503